Topological dynamics algorithms for enhanced cybersecurity protocols - Lenka, Reena Mahapatra; Tiwari, Sudhakar; Dommari, Sandeep; Bhosale, Varsha Kiran; Dass, Pranav; Chavan, Nikita; Tandon, Nitin (Journal of discrete mathematical sciences & cryptography, 2025)
Topological dynamics is a way to look at the features of changing systems through the lens of topology. It has a lot of potential for making security measures better. This method takes advantage of the structure and behaviour of networks to better find, stop, and deal with cyber risks. These algorithms can find strange things and possible security holes that other methods might miss by describing the physical features of network data and how systems interact with each other. Additionally, topological dynamics can help create security measures that change in response to new threats, making them a strong defense against cyberattacks that get smarter all the time. By adding these methods to cybersecurity protocols, it will be easier to find and stop complicated, sneaky attacks like Advanced Persistent Threats (APTs) and zero-day breaches. Topological dynamics methods allow for a more complete and proactive security stance by recording the global and local changes in how networks behave. This abstract talks about how topological dynamics could change cybersecurity. It stresses the need for more study and development in this new area to protect important digital systems and private data as the digital world changes all the time.